Application of the Money Laundering Law to Corruption Crimes - Sri Rizki Wardani; Galih Pratama Siregar (AT-TAFAHUM: Journal of Law, 2022)
This study examines the application of the Anti-Money Laundering Law (AML) in handling corruption in Indonesia. Corruption not only results in state financial losses but is also often accompanied by perpetrators' attempts to conceal the proceeds of crime through money laundering mechanisms. Therefore, the AML Law plays a strategic role as a legal instrument in tracing, freezing, and confiscating assets resulting from criminal acts. This study uses a normative juridical method with a statutory approach and case analysis. The results show that the application of the AML Law can broaden the scope of law enforcement, not only against the main perpetrators but also parties involved in the flow of illegal funds. In addition, the reverse burden of proof mechanism makes it easier for law enforcement officials to identify irregularities in the perpetrators' assets. However, its implementation still faces various obstacles, such as weak coordination between institutions and the complexity of tracking financial transactions. Therefore, optimizing the application of the AML Law is necessary to increase the effectiveness of corruption eradication and support the recovery of state losses.